Daffodils and Solitude in William Wordsworth’s I Wandered Lonely as A Cloud - Ni Komang Arie Suwastini; Pande Eka Putri Pradnyani (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2023)
PurposeThis study aims to identify the meaning of Wordsworth’s poem entitled I Wandered Lonely as a Cloud by analyzing its intrinsic elements. MethodThe present study is qualitative interpretive, focusing on the meaning conveyed in the poem entitled I Wandered Lonely as a Cloud using objective approach by interpreting the poem’s intrinsic elements through repeated reading of the poem as a whole and its details to achieve trustworthy analysis and conclusion. Results/findingsDifferent from general trend in the analysis Wordsworth’s I Wandered Lonely as a Cloud, the meaning of the poem is the experience of recalling the sight of the daffodils, which brought solitude to the speaker of the poem. The poem’s subject was not the daffodils, but the experience of encountering them and its recollection. As a traveler traveling in the countryside, the speaker viewed the sight of the daffodils in a positive tone through imageries of sight, internal sensation, and muscle movements related to good experiences, as well as dictions of natural views with positive connotations. The poem includes simile, personification, metonymy, and symbols to compare the beautiful crowd of daffodils and the solitude they bring to the speaker of the poem’s mind when he was recalling the sight of the dancing daffodils. ConclusionUsing Abram’s objective point of view, the analysis reveals the daffodils as representative of nature become the remedy for human’s loneliness as represented by the speaker of the poem by recalling the experience of seeing them, sending the message that appreciation of nature and the experience with nature should be maintained to create a tranquil life.